The postmodern challenge to clarity: The meaning of George Orwell’s Politics and the English Language for adult education theory - Stephen Brookfield (Adult Education Research Conference, 1996)
The ascent of postmodernism has brought with it questions about the possibility of clarity of communication in language, both written and spoken. "Saying what you mean" is seen as a modernist illusion, obscuring the fact that all discourse is subject to multiple readings. Critical pedagogues view calls for clarity of expression in academic writing as either politically naïve or camouflage for a conservative agenda. In his essay "Politics and the English Language" Orwell argues the counterviewpoint: that a lack of clarity in language permits the furtherance of repressive, fascist and totalitarian political agendas.